Marginal bone loss rates in screw-implant and cementation-implant supported prostheses: Tingkat kehilangan tulang marginal pada prostesis dukungan implan sekrup dan implan sementasi - Anshori, Nuriani; Jubhari, Eri Hendra; Dammar, Irfan (Makassar Dental Journal PDGI Makassar, 2024)
In the field of restorative dentistry, dental implants are very popular. There are two options for implant permanent crown restora-tion, screwed or cemented. Bone loss around the implant that occurs after one year of prostheses placement is one of the indica-tors for assessing treatment success. This article examines the marginal bone loss rates of both types of implant-supported pros-theses by collecting several internet-based literatures using the keywords marginal bone loss of implant screwed and implant ce-mented. The rate of bone loss is one of the assessments of the success of edentulous treatment using implants. There are seve-ral factors that impact bone loss around the implant. In screw implant prostheses marginal bone loss can be greater due to greater non-axial transfer of occlusal load and can be exacerbated if the implant is placed in an area that received a bone graft. It was concluded that greater marginal bone loss occurs with screw implant prostheses, but in terms of strength, screw implant pros-theses are better than cementation implant prostheses.